The impact of communicating liking on the formation of children's friendships. - Murphy, Kevin. (University of Ottawa (Canada), 1990)
It was hypothesized that the communication of liking between children may play an important role in the development of friendships. In an initial study, 65 children were interviewed concerning the behavioral basis for their own impressions regarding who liked or disliked them in their peer group. These same children also rated a set of behaviors in terms of the inference (of level of liking) they would likely make if a hypothetical new classmate had directed that behavior toward them. 22 behaviors were tentatively identified as being among the more important cues used by children in judging the level of liking other peers had for them. To confirm the communicative potential of these behaviors another sample of 260 grade-5 students read a series of hypothetical vignettes. In each vignette a single behavior taken from this set of 22 behaviors, its opposite, plus a neutral incident constituted the evidence available to children for inferring the level of liking between characters. The 16 positive behaviors from Study 1 all led to inferences of liking that were significantly more positive than the neutral point on the rating scales. The negative behaviors led to significant inferences of disliking. These behaviors were then incorporated into a measure of behavioral communication of liking. This scale was designed as a peer-report measure in which children were asked to rate how many times every other classmate had directed each of these behaviors toward them within a clearly defined time period. Psychometric properties considered included factor structure, internal consistency, construct as well as predictive validity. Results suggest that this scale is capable of generating a fairly good measure of children's behavioral tendencies to convey liking toward other peers. Patterns of correlations between measures in Study 3 were also examined to see if these supported the proposed model for this research. Results support a conclusion that the behaviors included on the Behavioral Communicators of Liking Scale are socially relevant and that an appreciable portion of the relational impact of these behaviors may be due to their ability to convey liking. The final study involved an experimental manipulation of relational communication in the context of a social skills training program. The primary criteria for selection into this intervention program was that the child had to have very few or no friends and display behavior patterns unlikely to convey liking toward their peers. Interventions featured both friendship skills coaching and ongoing relationship problem solving focusing. Significant treatment-related improvements were found in terms of how much peer friendship targets liked the children enrolled in this social skills training program, in these friendship targets' impressions regarding how much treatment children liked them, and in the ratings treatment children received from their friendship targets on the positive behavioral communication factor, in the development of children's friendships. (Abstract shortened by UMI.)
Keywords: Psychology, Social.